PENGARUH FIRM SIZE, PROFITABILITAS, STRUKTUR MODAL, KEBIJAKAN DIVIDEN, GCG, DAN CSR TERHADAP NILAI PERUSAHAAN PADA SEKTOR FINANCE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2017 - CHOIRUL UMAM, ARIDHO; HARTONO, ULIL (Jurnal Ilmu Manajemen (JIM), 2019)
The purpose of this study is to determine the influence of firm size, profitability, capital structure, dividend policy, GCG and CSR on firm value. The type of this research using quantitative research. Sampling technique is using purposive sampling. Data collection is done through documentation from finance sector period 2014-2017 which listed on BEI. Statistical analysis used in this study is to use SPSS. Technical data analysis in this study using the classical assumption test, multiple linear regression analysis and hypothesis testing. The result of analysis shows that firm size has a positive influence on firm value. Profitability have negative influence on firm value. Capital structure has no influence on firm value. Dividend policy has a positive influence on firm value. Managerial ownership has no influence on firm value. Institutional ownership has a influence effect on firm value. Independent commissioner has no influence on firm value. CSR have a positive influence on firm value.